Development of hermetic glass frit encapsulation for perovskite solar cells - Seyedali Emami (2019)
A hermetic laser-assisted glass frit encapsulation, at a process temperature of 120 degrees C, was developed for perovskite solar cell application. The hermeticity and long-term stability of the sealing was examined based on standard tests for photovoltaic (PV) applications. Encapsulations using fluorine doped tin oxide (FTO)-coated glass substrates displayed 8.93 x 10(-8) atm center dot cm(3) center dot s(-1) air leak rate after five cycles of a humidity-freeze test according to the IEC61646 standard; a rate lower than the reject limit of the MIL-STD-883 standard test for fine leaks. Devices sealed with a TiO2 blocking layer and FTO scribing-denoted as an empty perovskite solar cell-showed that the encapsulation is compatible with the various thermal coefficient of expansion regions of perovskite solar cells (PSCs). The applicability of the MIL-STD-883 standard was studied in detail and it was concluded that a new method is required to measure the fine helium leak rate of devices with cavity sizes larger than 5.5 x 5.5 cm(2). The developed sealing process is scalable for larger devices; therefore, it guarantees a new step forward for the industrialization of PSCs.